2004
DOI: 10.1152/jn.00261.2004
|View full text |Cite
|
Sign up to set email alerts
|

Resurgent Na Currents in Four Classes of Neurons of the Cerebellum

Abstract: Action potential firing rates are generally limited by the refractory period, which depends on the recovery from inactivation of voltage-gated Na channels. In cerebellar Purkinje neurons, the kinetics of Na channels appear specialized for rapid firing. Upon depolarization, an endogenous open-channel blocker rapidly terminates current flow but prevents binding of the “fast” inactivation gate. Upon repolarization, unbinding of the blocker produces “resurgent” Na current while allowing channels to recover rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 53 publications
(26 reference statements)
11
111
2
Order By: Relevance
“…This resurgent I Na is proposed to promote repetitive firing by rapidly restoring VGSC availability (32). We found that resurgent I Na was reduced in 14 DIV Scn1b null CGNs (P = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 65%
“…This resurgent I Na is proposed to promote repetitive firing by rapidly restoring VGSC availability (32). We found that resurgent I Na was reduced in 14 DIV Scn1b null CGNs (P = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 65%
“…3 E, F ) (see below). In contrast, use of a lowered external sodium concentration (15 mM in the current study) to improve the space clamp may have reduced the slope factor, as has been found for cerebellar neurons (Afshari et al, 2004). Additionally, the shallow slope is consistent with the presence of multiple sodium channels with slight differences in the voltage dependence of inactivation, thereby extending the voltage range over which inactivation occurred.…”
Section: Transient Sodium Current In the Pre-bötzinger Regionmentioning
confidence: 55%
“…The extracellular solution contained the following: 20 mM NaCl, 10 mM HEPES, 2 mM BaCl 2 , 300 M CdCl 2 , 140 mM tetraethylammonium-Cl, at pH 7.4. This low (20 mM) sodium concentration was used to improve control of the cell membrane voltage during voltage-clamp experiments on Purkinje neurons, which produce large sodium currents (Afshari et al, 2004). For recording resurgent currents, sodium concentration in the extracellular solution was raised to 50 mM to produce larger currents that could be analyzed more accurately and tetraethylammonium-Cl was reduced to 110 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Resurgent sodium current, a component of sodium current that flows transiently on repolarization of the cell, has been identified in cerebellar Purkinje neurons and other central neurons (Raman and Bean, 1997; Afshari et al, 2004;Do and Bean, 2004). Like the persistent sodium current, resurgent current has been implicated in promoting fast repetitive neuronal firing in these neurons Bean, 1997, 1999a; by accelerating depolarization toward threshold between action potentials (Raman and Bean, 1999a).…”
Section: Reduced Resurgent Sodium Current In Purkinje Neurons Of Het mentioning
confidence: 99%